Effect of hypertonic conditions on protein synthesis in cells productively infected with simian virus 40. - England, J M (1975)
Hypertonic medium selectively suppressed the synthesis of most host cell polypeptides relative to the synthesis of simian virus 40 capsid polypeptides and a minority of cellular polypeptides, notably histones. Under optimal hypertonic conditions, the synthesis of the major capsid polypeptide (VP1) is enhanced about sevenfold relative to host polypeptide synthesis. Because of the small amounts of the other nonhistone capsid polypeptides (VP2) and VP3) present in cell lysates, it was difficult to quantitate the extent, if any, of their enhancement. The maintenance of the restricted pattern of protein synthesis caused by hypertonic medium was dependent on continual peptide chain initiations. The resistance of viral protein synthesis to hypertonic conditions provides a means of detecting relatively low levels of intracellular viral protein synthesis. Analysis of the specific activity of the acid-soluble [3H]lysine pool indicated that the rate of incorporation of [3H]lysine into protein was an overestimation of the actual rate of overall protein synthesis occurring in cells exposed to hypertonic as compared to isotonic conditions. Since it is likely that both cellular and viral protein synthesis draw lysine from a single pool, this change in pool specific activity does not affect the analysis of relative rates of protein synthesis at a given level of tonicity.